Improving on 'Data Mining Reconsidered' by K. D. Hoover and S. J. Perez. - Hendry, D; Krolzig, H (Blackwell Publishing, 1999)
Kevin Hoover and Stephen Perez take important steps towards resolving some key issues in econometric methodology. They simulate general-to-specific selection for linear, dynamic regression models, and find that their algorithm performs well in re-mining the "Lovell database";. We discuss developments that improve on their results, automated in PcGets. Monte Carlo experiments and re-analyses of empirical studies show that pre-selection F-tests, encompassing tests, and sub-sample reliability checks all help eliminate "spuriously-significant" regressors, without impugning recovery of the correct specification.